Determinants of financial shortfalls in state-owned railway systems: an ARDL approach for Sri Lanka railways - Danthanarayana, C.T.; Francis, S.J.; Kumarage, A.S. (University of Jaffna, 2024)
Sri Lanka Railways (SLR) has been experiencing a financial shortfall since the 1940s, characterised by operational expenditure exceeding total revenue. This study aimed to identify the critical determinants of the financial shortfall of Sri Lanka Railways (SLR) using an econometric approach. Employing a quantitative methodology, the study utilised secondary and manipulated data from 1977 to 2022 to examine the effects of four key variables: revenue shortfall from fare revisions (FRFR), subsidised season tickets (FRSS), freight transport volume (FTK), and total wage bill (WB), incorporating the general price level (CCPI) to account for inflation. The regression analysis, using the Auto Regressive Distributed Lag Model, identified a short-run relationship between the financial shortfall (LFS) and lagged variables, including the volume of rail freight transport (LFTK), total employee wage bill (LWB), and the general price level (LCCPI). A long-run relationship was found among revenue shortfall from fare revisions (LFRFR), LWB, LCCPI, and LFS. The findings highlight the significant impact of aligning railway fares with bus fares and managing employee expenses on SLR's financial shortfall. Additionally, the revenue shortfall from subsidised season tickets showed a significant relationship at a 10% significance level, both short-term and long-term. The study underscores the necessity of revising railway fares in line with bus fares to enhance revenue and ensure financial sustainability. Optimising employee-related costs through effective management and reviewing the subsidy structure for season tickets are also recommended. Furthermore, investment in capacity and facility development for freight transport is crucial for mitigating long-term financial shortfalls.
Keywords: Auto Regressive Distributed Lag Model; Financial Shortfall; Sri Lanka Railways